Helmholtz-Structured Two-Dimensional Super-Diffraction Meta-Lens - Li, He-He; Zheng, Bo; Duan, Mu-Sen; Han, Feng; Hu, Yun-Xin; Li, Xiao-You; Qian, Si-Yu; Chen, Xue-Feng; Liu, Sheng-Chun (Frontiers in Physics, 2022)
Focusing beyond the acoustic diffraction limit has always been expected, especially in acoustic imaging and ultrasonic therapy. Manipulating the acoustic waves beyond the diffraction limit offers an alternative application potential in high-resolution imaging and medical ultrasound diagnosis and treatment. Here, a two-dimensional circular meta-lens is presented, with a sub-wavelength acoustic Helmholtz resonator array to implement the super-diffraction focusing. The proposed acoustic meta-lens consists of 28 units, which possesses the ability to yield designed arbitrary phase shifts and maintain the impedance matching to provide the high sound transmission efficiency. The simulation and experimental results show that the designed acoustic meta-lens can realize subwavelength sound focusing beyond the diffraction limit. The proposed method can greatly promote the application and development of the acoustic superfocusing technology in acoustic imaging, particle manipulation, and other fields.